Peptic ulcer disease in children - Sullivan, P (2010)
Peptic ulcer disease is uncommon in children with an estimated frequency of 1 case in 3000 hospital admissions. In children, peptic ulcer disease is usually classified as either primary or secondary depending on the underlying pathology. Helicobacter pylori infection of the stomach is the commonest cause of primary peptic ulcers. Other causes of primary ulcers include those caused by rare conditions of acid hypersecretion such as Zollinger-Ellison syndrome; G-Cell hyperplasia; systemic mastocytosis; short bowel syndrome; and hyperparathyroidism. Secondary ulcers occur more often in younger children. They have a worse prognosis and are usually associated with physiological stress and systemic illness such as sepsis, head trauma, burns, sickle cell disease, type I diabetes, systemic lupus erythematosus and drug therapy. Upper gastrointestinal endoscopy is the investigation of choice for children with suspected peptic ulcer disease. Triple therapy given twice daily with a proton-pump inhibitor plus two antibiotics (e.g. Metronidazole plus Amoxicillin or Amoxicillin plus Clarithromycin) for two weeks will eradicate H. pylori and heal ulcers in the majority of cases. © 2010 Elsevier Ltd.